A Germacalicene: Synthesis, Structure, and Reactivity. Issue 4 (20th December 2018) - Dong, Zhaowen; Albers, Lena; Schmidtmann, Marc; Müller, Thomas
Abstract: The synthesis of the germacalicene7 from the reaction of the dipotassium germole dianion K2 [6 ] with 1, 2‐bis‐diisopropylamino‐3‐chlorocyclopropenyl perchlorate is reported. Based on the crystal structure analysis and the results of DFT calculations, the germacalicene7 can be viewed as a cyclopropenium germacyclopentadienide ylide that is isoelectronic to α‐cationic phosphanes. First reactivity studies revealed its nucleophilic character and resulted in the isolation of the air‐ and moisture‐stable carbonyl iron complex15 and the cationic silver complex20 . One‐electron oxidation of the germacalicene7 was achieved by its reaction with [Ph3 C][B(C6 F5 )4 ] and the bis‐cationic Ge−Ge‐bonded dimer22 was isolated. Abstract : Ylidic reactivity : Germacalicene is, in contrast to calicene, a non‐planar compound and is best described as a germanium/carbon ylide (see figure). Its reactivity is dominated by the lone pair at the germanium center.